2017
DOI: 10.1017/s1355770x17000341
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between livestock grazing practices, disease risk, and antimicrobial use among East African Agropastoralists

Abstract: Livestock health is economically important for agropastoral households whose wealth is held partly as livestock. Households can invest in disease prevention and treatment, but livestock disease risk is also affected by grazing practices that result in inter-herd contact and disease transmission in regions with endemic communicable diseases. This paper examines the relationships between communal grazing and antimicrobial use in Maasai, Chagga and Arusha households in northern Tanzania. We develop a theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…In addition, many epidemiological models entirely ignore the effects of changing prevalence on privately optimal spending on disease control (22,23). However, several empirical studies have shown that a farmer's likelihood to take control actions is the result of a dynamic and complex interplay between epidemiological, economic, environmental, cultural, and social factors (39)(40)(41)(42)(43). Models of disease transmission that ignore such heterogeneity are likely to be misleading, resulting in reduced value for informing control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many epidemiological models entirely ignore the effects of changing prevalence on privately optimal spending on disease control (22,23). However, several empirical studies have shown that a farmer's likelihood to take control actions is the result of a dynamic and complex interplay between epidemiological, economic, environmental, cultural, and social factors (39)(40)(41)(42)(43). Models of disease transmission that ignore such heterogeneity are likely to be misleading, resulting in reduced value for informing control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Poor or nonexistent road infrastructure and public transportation, or seasonal weather conditions can exacerbate accessibility problems [33]. The same is true for animal health services where veterinarians and animal health workers need to travel to remote areas in order to attend farmers [34]. Retail shops tend to be located nearer to patients and clients than institutional health facilities, especially in rural areas, and often become the only source of care [17][18][19]25,31].…”
Section: Accessibilitymentioning
confidence: 99%
“…Affordability impacted decisions on antimicrobial use in studies in northern Tanzania [34] and Kenya [28]. In Caudell and colleagues' (2020) study, a Kenyan farmer explained that most money in his household is spent on food and medicines, which leaves little for biosecurity and infection prevention [18].…”
Section: Affordabilitymentioning
confidence: 99%
“…Disease incidence may also affect future costs, increase subjective disease risk assessment, and result in increased future use of preventive medications. Increased use of antibiotics is of concern in relation to the emergence and spread of antimicrobial resistance, which may be costly for the society as a whole (Ahmed et al, 2018;Althouse et al, 2010). There may be several other costs related to livestock management and disease control.…”
Section: Indirect Impacts Of Livestock Diseasementioning
confidence: 99%